Effect of ‘Results Waiting Areas’ in the Emergency Department using Vertical vs. Horizontal Patient Flow on Bed Occupancy and Staff/Patient Satisfaction: A Quasi-Experimental Study (Bangladesh Journal of Medical Science, 2026)
Background Overcrowding is a widespread global concern that can adversely affect patient satisfaction and outcomes in the emergency department (ED). The aim of this study was to evaluate the effect of ‘Results Waiting Areas’ in the ED, using horizontal versus vertical patient flow on bed occupancy and staff/patient satisfaction. Material and Methods This was a quasi-experimental study that investigated the effect of implementing a “results waiting area” using a vertical patient flow approach versus a horizontal patient flow approach in the ED of a hospital in Sari, Iran. In the vertical patient flow group, a dedicated “results waiting area” was created within the existing ED space. This involved removing the horizontal stretchers and replacing them with multiple chairs that allowed patients to be assessed and receive medical management while in an upright sitting position. Results A total of 156 patients with a mean age of 32.44 ± 17.96 years participated in the study. 72 patients were in the vertical flow group, and 84 were in the horizontal flow group. 66.03% were male, and 52.26% were married. The staff satisfaction rate was significantly higher in the vertical flow group (83.3%) compared to the horizontal flow group (29.7%). There was also a significant difference in patient satisfaction, which was higher in the horizontal flow group (p=0.016). In the horizontal flow group, there was a significant relationship between patient satisfaction with fast and timely admission and the number of patients hospitalized per day (p=0.002). Conclusion The mean length of stay in the ED was significantly longer in the vertical flow group, but the ED was more crowded in the horizontal flow group. Overall, staff satisfaction was significantly higher with the vertical patient flow method compared to the horizontal method.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 812-820